Biomechanical report for the IAAF World Championships London 2017 4 x100 m Relay Men's - Pollitt, L.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The winning time of 37.47 s for Great Britain & N.I. was an impressive achievement as in addition to a new world leading time and season's best, it meant a new personal best mark that eclipsed their own 18-year European record by 0.26 s; recorded at the 1999 World Championships in Sevilla. Christian Coleman anchored the United States home in 37.52 s for his second silver medal of the championships. Although Jamaica trailed Great Britain & N.I. out of the final transition by only three tenths, Bolt could not add to his 19 medals as he pulled up early in the home straight with severe hamstring cramps. Japan capitalised to secure bronze in 38.04 s. Great Britain & N.I. and the United States also recorded the fastest times during the heats, except for a role reversal. As in the heats, Great Britain & N.I. led from the start. However, in the final they were able to maintain this to the finish. Their chequered history of disqualification for poor handovers and dropped batons was vanquished by outstanding consistency within the transitions. Great Britain & N.I.'s polished performance within transitions during the final was highlighted by a large improvement from the heats (0.210 s), and exceptional consistency (variance of 0.6%). Even though the United States also displayed similar consistency (variance 1.1%), they were slightly less efficient (0.115 s) in key elements contributing to the handover, which unfolded to be the pivotal factor as it accounted for the exact winning margin by the finish. Great Britain & N.I. were also notably more efficient than Jamaica within transitions (0.350 s), and despite Bolt's issue, it appears unlikely that even he could have changed the outcome of the race. Great Britain & N.I.'s improvement through transition 3 compared to their heat (-0.055 s) also enabled Mitchell- Blake to exit the transition with a greater margin to hold off the challenge of Coleman. The time recorded by Great Britain & N.I. within transitions 1 and 3 (1.855 s), was the joint fastest time of the final, with Canada (transition 2) and the United States (transition 3). Interestingly, the most efficient transition of the championships was recorded by Canada during the heats (1.805 s), which also included the second fastest handover of the heats (0.150 s). However, the fastest handovers did not necessarily coincide with the fastest transition times. Great Britain & N.I. produced the fastest handover of the championship (0.105 s) within transition 2; their longest transition time (1.875 s) of the final. And despite identical times for transitions 1 and 3, the handover in transition 1 was more than double that of transition 3 (0.350 s vs. 0.165 s). With respect to consistency, the lowest variance in handover duration during the final (13.9%) was recorded by the United States, yet this did not result in the quickest transition times. Nevertheless, the quick handover within the final transition for Great Britain & N.I., compared to the heats (0.165 s vs. 0.510 s), may have been a key factor that contributed to achieving a faster transition; which ultimately provided Mitchell-Blake with a large enough margin to hold off Coleman and secure gold. With clear inconsistencies across teams, the handover duration may therefore not be the pivotal factor to an efficient transition. Another related key factor, could be the timing of the handover. For example, the United States (~15%) and Jamaica (<15%) began the handover early into each transition. By transition 3, this could serve to maximise the potential of the athletes running the final leg (Coleman and Bolt). Great Britain & N.I. on the other hand displayed a progressive trend over consecutive transitions (20.5% to 38.5%). In comparison to the United States and Jamaica, the later handover position in transition 3 may have enabled Mitchell-Blake to achieve an optimal running speed during the handover which ensured near maximal speed at transition exit. It is also possible that Great Britain & N.I.'s tactics were to maximise their strengths whilst nullifying the strengths of their main challengers before the race (United States and Jamaica). Having their fastest athlete (Chijindu Ujah) on the first leg gave Great Britain & N.I. the lead into and out of transition 1. The challenge on the back and home straights was to minimise the loss in time to the United States who fielded the individual 100 m gold and silver medallists respectively (Justin Gatlin and Christian Coleman). This tactic may have been executed to perfection, as the time loss (0.205 s) was neutralised on the bends (i.e., legs 1 and 3). Despite the unrivalled success in previous championships, Jamaica's key athletes (Blake and Bolt) were not in top form. Jamaica drafted in 110 m hurdles champion (Omar McLeod) to lead out, and while this saw an improvement from the heats in the 100 m split time (0.100 s) and an individual leg split time comparable to Great Britain & N.I. and the United States, they trailed Great Britain & N.I. into the transition (0.125 s) and were further behind by transition exit (0.195 s). By the time Yohan Blake exited transition 2 for Jamaica, greater efficiency within the transitions enabled Great Britain & N.I. to maintain this advantage. This difference cost Jamaica a combined loss of 0.350 s over the three transitions. A key influencing factor may have been the shorter time spent by the receive leg within the transition before baton entry (5-9%) compared to both Great Britain & N.I. (11-15%) and the United States (8-15%). It may have resulted in the delivery leg having to break and slow before handover to match the slower speed of the receive leg; a variable that may be an important consideration during future competitions. In summary, the outcome of the men's relay was decided by greater efficiency throughout the transition phases. By completing the handover later in the transition, Great Britain & N.I. may have been able to maintain a higher consistency of running speed. Despite having individual gold and silver medallists from the individual 100 m, the approach to complete the handover early within the transition did not appear to allow the United States to take full advantage of this. For the other teams, including bronze medallists Japan, a consistent loss of time within transitions likely explains further time loss between the transitions. (Attention! registration on the IAAF site is required for downloading)